The Origin Of Virtue Ethics: Aristotle’s Views - Abakare , Chris (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
There has been a current revival of interest in virtue ethics as a credible moral theory. There has been some displeasure with the way many modern moral theories emphasize moral obligation and law at the expense of an individual. Therefore, virtue ethics stands as one of the foremost and important moral theories in ethics. This research will examine the perspective of virtue ethics as a credible moral theory. Specifically, this paper aims at highlighting and critiquing the importance of Aristotle’s model of virtue ethics. Firstly, this paper provides a summary of virtue ethics theory and addresses the central tenets of Aristotle’s ethical theory. Here, different types of Aristotelian virtues; cardinal virtues (courage, practical wisdom/phronesis, justice, temperance), and the concepts of eudaimonia and golden mean were examined. Finally, the paper critiqued Aristotle’s virtue ethics.